Institutional research capacity development for integrated approaches in developing countries: An example from Vietnam - Hung Nguyen-Viet; Vi Nguyen; Phuc Pham Duc; Le Vu Anh; Phung Dac Cam; Tanner, M.; Grace, Delia; Zurbrugg, C.; Tran Thi Tuyet Hanh; Tu Vu-Van; Luu Quoc Toan; Dang Xuan Sinh; et al. (CAB International, 2015)
This chapter presents the Vietnamese experience on developing institutional capacity for integrated research in developing countries. The emergence of a research group in environmental health, which was rooted from a North-South partnership research programme in Switzerland, is described, discussing in detail how it developed and became integrated as a national institution, as well as its work in addressing local needs and informed policy.